2013
DOI: 10.1557/jmr.2012.392
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 nanotubes and its composites: Photocatalytic and other photo-driven applications

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 101 publications
0
19
0
Order By: Relevance
“…1−7 TiO 2 nanotube (TNT), a typical one-dimensional nanostructure, possesses unique geometrical characteristics and advantages in the photocatalytic application due to its large surface-to-volume ratio, direct pathways for charge transport, good mechanical stability, and rich activity sites for pollutant degradation. 8,9 However, it can only utilize no more than 5% of total solar energy irradiating on the earth surface due to its wide bandgap and exhibits high recombination rate of photogenerated electron/hole pairs, which restrict the wide application of TNT in the semiconductor photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…1−7 TiO 2 nanotube (TNT), a typical one-dimensional nanostructure, possesses unique geometrical characteristics and advantages in the photocatalytic application due to its large surface-to-volume ratio, direct pathways for charge transport, good mechanical stability, and rich activity sites for pollutant degradation. 8,9 However, it can only utilize no more than 5% of total solar energy irradiating on the earth surface due to its wide bandgap and exhibits high recombination rate of photogenerated electron/hole pairs, which restrict the wide application of TNT in the semiconductor photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, the electrochemical anodization of titanium in fluorinated electrolytes is a simple method to synthesize porous highly vertically ordered structures with high aspect ratios. The process of self organization of nanotube is a complex mechanism [10]- [13] and requires extensive study. The properties of self-organized TNA can be tailored using various anodization conditions and post deposition treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] For example, Lv et al successfully designed and synthesized pure brookite, anatase, and mixed-phase TiO 2 via hydrothermal reaction by adjusting pH values. It was found that mixed-phase TiO 2 exhibited the best photocatalytic activity especially when the sample was prepared under pH 5 8.…”
Section: Resultsmentioning
confidence: 99%